2014
DOI: 10.1007/s12640-014-9482-z
|View full text |Cite
|
Sign up to set email alerts
|

DSP4, a Selective Neurotoxin for the Locus Coeruleus Noradrenergic System. A Review of Its Mode of Action

Abstract: DSP4 (N-(2-chloroethyl)-N-ethyl-2-bromobenzylamine hydrochloride) is a selective neurotoxin for the locus coeruleus noradrenergic system in the rodent and bird brain. It readily passes the blood-brain barrier and cyclizes to a reactive aziridinium derivative that is accumulated into the noradrenergic nerve terminals via the noradrenaline transporter. DSP4 is also an irreversible inhibitor of this transporter. Within the nerve terminals the aziridinium derivative reacts with unknown vital cellular components, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 93 publications
2
86
0
Order By: Relevance
“…It is possible that increased activation of the remaining cells was sufficient to reduce inflammation and increase locomotion, and it has been shown that remaining LC-NE cells after DSP-4 lesion can act in a hyperactive manner to re-innervate targets [43]. Additionally, neuronal loss after DSP-4 occurs later than NE terminal loss in LC target regions [44,45], suggesting that VNS in our model may act in a neuroprotective manner to prevent LC-NE loss in lesion VNS rats. Future studies are necessary to determine whether the improvements observed in our model are due to protective effects of VNS or increased activation of remaining LC-NE neurons.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that increased activation of the remaining cells was sufficient to reduce inflammation and increase locomotion, and it has been shown that remaining LC-NE cells after DSP-4 lesion can act in a hyperactive manner to re-innervate targets [43]. Additionally, neuronal loss after DSP-4 occurs later than NE terminal loss in LC target regions [44,45], suggesting that VNS in our model may act in a neuroprotective manner to prevent LC-NE loss in lesion VNS rats. Future studies are necessary to determine whether the improvements observed in our model are due to protective effects of VNS or increased activation of remaining LC-NE neurons.…”
Section: Discussionmentioning
confidence: 99%
“…However, acute high-intensity exercise was sufficient to overcome the attenuation by DSP-4, presumably via pathways that are independent of LC-norepinephrine such as glutamatergic or serotonergic synaptic activity. Indeed, serotonin signaling may also be important for exercise-induced Bdnf expression (Ivy et al 2003;Russo-Neustadt et al 2004) and DSP-4 is reported to leave serotonergic signaling intact (Ross & Stenfors 2014). Because we did not include a home-cage control group, we are unable to determine if the treadmill environment alone was sufficient to increase total Bdnf and Bdnf IV mRNA.…”
Section: Glutamate Receptorsmentioning
confidence: 97%
“…DSP-4 has been shown to reduce tissue levels of norepinephrine in regions innervated by the LC, such as the hippocampus (Anisman et al 1984;Archer et al 1982;Bennett et al 1990;Jonsson et al 1981;Ögren et al 1980;Ross 1976;Scullion et al 2009;Szot et al 2010;Zahniser et al 1986), though leaves non-LC NA neurons and serotonergic and dopaminergic systems essentially unaffected (Ross & Stenfors 2014). This chemical is commonly used to irreversibly disrupt central NA signaling because it easily crosses the blood brain barrier and therefore can be injected systemically (Ross & Stenfors 2014). The DSP-4 (Sigma Aldrich, St. Louis, Mo, USA) was prepared in 0.9% saline and a single 50 mg/kg dose was delivered by IP injection in a volume of 10 ml/kg; a dose frequently used in rodents and shown to be effective in depleting hippocampal norepinephrine (Ross & Stenfors 2014).…”
Section: N-(2-chloroethyl)-n-ethyl-2-bromobenzylaminementioning
confidence: 99%
See 1 more Smart Citation
“…The main DSP4 neurotoxic mechanism of action involves noradrenergic neurotransmission, although one work has reported decreased serotonin levels in the cerebellum of rat brains and in the spinal cord (Jonsson et al, 1981), which is in agreement with our results. Several reports describe noradrenaline levels decrease in cerebral regions after systemic injections of DSP4, whereas many other reports from microdialysis state that extracellular noradrenaline levels are actually increased (for review see Ross and Stenfors, 2015). Therefore, the antidepressant-like effect of DSP4 per se could be explained by increased extracellular levels of noradrenaline in some particular brain regions, although the overall levels of noradrenaline are decreased (as shown in HPLC results).…”
Section: Discussionmentioning
confidence: 92%